Performance, feed quality and P response of Leucaena and Calliandra species grown as hedgerows on an acidic nitosol at Soddo, Ethiopia - Berhe, Kahsay; Tothill, J.C. (1995)
Eleven accessions taken from Leucaena leucocephala, L. revolutal, L. pallida, L. diversifolia and L. leucocephala × L. diversifolia hybrids (leucaena), together with 3 accessions of Calliandra calothyrsus (calliandra), were evaluated on an acidic, nitosol soil in the tropical highland region of Soddo in southern Ethiopia for dry matter production, feed quality, soil fertility and responses to phosphorus fertilisation. At the first harvest (11 months after transplanting), over all accessions and for individual accessions, plant height, spread, basal stem diameter and dry matter yield showed significant responses to the application of phosphorus (P). There was also a significant interaction between accessions and P treatments for most of these growth parameters. Two regrowth harvests showed a significant response in dry matter production of both leaf + soft stem and hard-stem fractions to the application of phosphorus (P). L. leucocephala accessions had higher in vitro dry matter digestibility (IVDMD) values than the other Leucaena spp. Two of the 3 C. calothyrsus accessions had significantly higher values for ash, NDF and ADF, lower IVDMD and slightly lower protein than all leucaena accessions. The clearly superior growth performance of the calliandras and the leucaenas, other than L. leucocephala, over that of cv. Peru (control), emphasises the need to evaluate their feed value in vivo and at the farm level. While already being used quite widely as a multi-purpose tree, calliandra has not been collected and researched much around the world as a forage species. There seems to be considerable scope for the selection of productive and useful lines of calliandra and L. diversifolia, L. pallida, L. revoluta and some of their hybrids for the cooler tropical highlands, for acidic soils and for potential psyllid resistance.